Vulvar carcinoma and its recurrences - principles of surgical treatment - Viktora, Libor; Minář, Luboš; Felsinger, Michal; Weinberger, Vít (Ceska gynekologie, 2022)
OBJECTIVE: A comprehensive overview of the surgical treatment of vulvar cancer, including recurrent forms. METHODOLOGY: A review work providing a basic overview of the pathogenesis, dia-gnosis and surgical treatment of vulvar cancer with a focus on the possibilities of treatment of its recurrences. It includes an illustrative case report presenting a patient with invasive squamous cell carcinoma of the vulva with iterative local recurrences and subsequent development of tumor triplicity and distant metastatic involvement. CONCLUSION: Surgical treatment remains the main modality of vulvar cancer therapy, even in the case of locally advanced or recurrent findings. In these cases, multidisciplinary cooperation of operational fields is necessary. The discipline of treated patients with participation in regular dispensary care plays an important role in the early detection of recurrences. (Chemo) radiotherapy remains a possible alternative to the surgical solution; in clinical practice, radiotherapy has an irreplaceable place in adjuvant therapy. Regional and distant recurrences are characterized by a poor prognosis.
Keywords: local recurrence; Carcinoma, Squamous Cell; Recurrence; Female; surgery; groin (inguinal) recurrence; Neoplasm Recurrence, Local; ženské pohlaví; vulvar cancer; lidé; staging nádorů; concurrent chemoradiotherapy; recidiva; nádory vulvy; distant recurrence; Vulva; Vulvar Neoplasms; operative treatment; retrospektivní studie; spinocelulární karcinom; lokální recidiva nádoru; Retrospective Studies; vulva; Neoplasm Staging; Chemoradiotherapy; Humans